STRATEGI MILITER DLAM PERANG KEMERDEKAAN DI YOGYAKARTA PADA TAHUN 1945-1949 - Muflihah, Wilda; Yunianto, Tri; Isawati, Isawati (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2016)
The study about the military strategic of independence war during 1945-1949 in Yogyakarta, aims to determine: (1) The situation in Yogyakarta (2) The strategy used during independence war in Yogyakarta (3) The impact of the independence war in Yogyakarta(4) The relevance of this study related to the course of Historical Education program in FKIP UNS.The research used historical method. The historical method is the process of critically examining and analyze the recordings and relics of the past. The initial stage in the process of historical research is the collection of data or heuristics. The research data was collected in the form primary and secondary data related to military strategy in the Independece War in Yogyakarta in periode 1945-1949. After data collection is completed then perform analysis activities. The data analysis phase from verification or criticism interpretating historiographical translation begins.Based on these results we can conclude that: (1) The political situation during 1945-1949 in Yogyakarta acts as military government after the second Dutch military aggression which led The president and several minister were caught. In carrying out their duties, The military government collaborated with civil government.Every guerrilla military action by TNI personnel, Dutch response with the cleaning action that damage people. The security situation in Yogyakarta during 1945-1949, several clashes occur between the people of Indonesia by Japanese and Netherlands, in addition to the peaceful of people also disrupted by the cleaning action that was done by Netherlands.(2) In the time of independence war the TNI soldier used guerrilla strategy combined with citizenry stronghold against Netherlands. The principal analysis of this study are the formulation, assessment, and implementation of the strategy. (3) The impact of the independence war in Yogyakarta was affected the attitude of the international community towards Indonesia and Netherlands. The UN and the countries, which support RI, pressing Netherlands to release political prisoners and restore Yogyakarta under Indonesia government immediately. (4) The relevance of military strategy in the independence war during1945-1949 in Yogyakarta is related to the course in Historical Education program in FKIP UNS which has compatibility to the material subject, citizenry and military freedom fighter of Indonesia, especially the endeavor in military field.